Spontaneous Spinal Epidural Hematoma: A Retrospective Study on Prognostic Factors and Review of the Literature - Fedor, Mark (Korean J Spine, 2011)
OBJECTIVES: The spontaneous spinal epidural hematoma (SSEH) is a rare clinical entity. Patients typically present with sudden onset back pain followed by neurological deficits. METHODS: Diagnosis of SSEH is usually made with MRI and standard treatment is surgical evacuation. In 1996, Groen published the most comprehensive review on the SSEH in which he analyzed 333 cases. We review 104 cases of SSEH presented in the English literature since the last major review and add three of our own cases, for a total of 107 cases. RESULTS: Our patients presented with back pain and neurologic deficits. Two made excellent functional recovery with prompt surgical decompression while one continued to have significant deficits despite evacuation. Better postoperative outcome was associated with less initial neurological dysfunction, shorter time to operation from symptom onset and male patients. CONCLUSION: We discuss the etiology of SSEH and report current trends in diagnosis, treatment, and outcome.